2018
DOI: 10.1111/twec.12715
|View full text |Cite
|
Sign up to set email alerts
|

Export product range and economic growth in theEUcountries

Abstract: We analyse the number of different HS8 products in the EU countries’ exports in 1995–2015. We review what share, or coverage, of the total possible number of these products the countries have exported each year. The EU15 countries have typically witnessed a slow rise in this coverage rate, that is, a widening of their extensive margins. The exception is Finland where the share has declined considerably. On the other hand, Ireland, Greece, Portugal and the new member countries have seen a dramatic increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Funke and Ruhwedel (2002) moreover also found that export diversification improves not only economic growth, but also overall export performance in OECD countries. Kaitila (2018) found that also in the case of Portugal that there is a significant relationship between the increase in the number of different export products and GDP growth.…”
Section: Why Do Exporting and Export Diversification Matter?mentioning
confidence: 93%
See 2 more Smart Citations
“…Funke and Ruhwedel (2002) moreover also found that export diversification improves not only economic growth, but also overall export performance in OECD countries. Kaitila (2018) found that also in the case of Portugal that there is a significant relationship between the increase in the number of different export products and GDP growth.…”
Section: Why Do Exporting and Export Diversification Matter?mentioning
confidence: 93%
“…Del Rosal (2018 found this also in the case of 28 EU countries, including Portugal 16. A growing literature has found empirical evidence supporting the relationship between export diversification and growth, amongst others Herzer et al (2006), Naudé and Rossouw (2011), Agosin et al (2007) and Kaitila (2018). Funke and Ruhwedel (2002) moreover also found that export diversification improves not only economic growth, but also overall export performance in OECD countries.…”
Section: Why Do Exporting and Export Diversification Matter?mentioning
confidence: 95%
See 1 more Smart Citation
“…Rosal (2018) found this also in the case of 28 EU countries, including Portugal. 18 A growing literature has found empirical evidence supporting the relationship between export diversification and growth, amongst others Herzer and Nowak-Lehnmann (2006), Naudé and Rossouw (2011), Agosin et al (2012) and Kaitila (2018). Funke and Ruhwedel (2002) moreover also found that export diversification improves not only economic growth, but also overall export performance in OECD countries.…”
Section: Why Do Exporting and Export Diversification Matter?mentioning
confidence: 96%
“…Funke and Ruhwedel (2002) moreover also found that export diversification improves not only economic growth, but also overall export performance in OECD countries. Kaitila (2018) found that in the case of Portugal that there is a significant relationship between the increase in the number of different export products and GDP growth.…”
Section: Why Do Exporting and Export Diversification Matter?mentioning
confidence: 98%